Optimizing technology-based business strategies for empowering community partnerships and improving the welfare of women farmers - Dwi Andini Putri; Dinar Ajeng Kristiyanti; Ratnawaty Marginingsih (University of Merdeka Malang, 2023)
In this era of technological advances, the rapid, accurate, and precise dissemination of information is crucial, especially for rural communities seeking to enhance their living standards. Farmer Women's Community (KWT) Al Mina Ciawi Village, established by a women's group in Ciawi Village, operates as a food and animal security program. Activities at KWT Al Mina Ciawi Village involve cultivating various hydroponic vegetables and catfish farming in buckets. However, a significant challenge lies in product sales during harvest, with agricultural and livestock products primarily marketed through WhatsApp and Instagram or waiting for direct buyers to visit the location. The primary aim of this community empowerment initiative is to optimize information technology for the betterment of KWT Al Mina and Ciawi Village. The program supports partners by offering e-commerce training to expand the marketing of KWT Al Mina products within the village. The chosen approach for e-commerce development is the Rapid Application Development (RAD) method, which includes website design planning, initial assessment, outreach, training, mentoring, and evaluation. The evaluation results affirm the program's success. KWT Al Mina members in Ciawi Village experiencing a remarkable 94% skill improvement in accessing technology, as indicated by pre-test and post-test assessments.